Estudo de diferentes precursores de fosfato na síntese de vidros bioativos 58S via rota sol-gel em meio básico - Silveira, Felix Raman Silva (2025)
This dissertation aims to evaluate the most effective precursor for incorporating phosphate into the structure of 58S glass nanoparticles, composed of 60% SiO2 – 36% CaO – 4% P2O5 (molar %), synthesized via a base-catalyzed sol-gel route. The tested phosphate precursors were triethyl phosphate (TEP), phytic acid (FIT), and dibasic ammonium phosphate (FOS). The methodology was adapted for FIT and FOS to preserve, as closely as possible, the synthesis conditions described in the literature for TEP. The silicate precursor (tetraethyl orthosilicate, TEOS) and calcium precursor (calcium nitrate, NaNO3) were kept constant. Among the precursors tested, FOS proved to be the most suitable for phosphate incorporation into the glass, achieving the nominal value without the formation of segregated crystalline phases after heat treatment and exhibiting the best performance in bioactivity. FIT exhibited crystallization issues during heat treatment, which did not significantly affect bioactivity but may impact cellular behavior. TEP, although unable to incorporate phosphorus, did not compromise bioactivity and was still capable of generating hydroxyapatite (HAp).